Socio-economic development of fishers in Andhra Pradesh and Telangana states in India - Ponnusamy, Kuppusamy; Sendhil, R.; Krishnan, M. (Indian Journal of Fisheries, 2016)
A study was conducted across Andhra Pradesh and Telangana states among 647 fisher households comprising five major sectors viz., brackishwater, freshwater, reservoir and marine fisheries as well as procurement and marketing sectors to understand the level of socio-economic development of fishers. Fishers development index (FDI) was constructed based on health, income and literacy dimensions. Analysis of data indicated that the literacy level was highest among marine fishers (51.45%), followed by brackishwater aquaculture (45.61%) and fish procurement and marketing sector (36.26%). Fishers in coastal areas tend to have better access to education than the fishers of inland water bodies. Incidence of common diseases (annual frequency) was more in the brackishwater aquaculture relative to other sectors in the study region. The position of educational and health status of fishers warrants a strong need to improve the access of fishers to health related services for overall development. High income from the marine sector and a relatively higher weightage (37%) to the income dimension played a major role for its FDI score. Freshwater aquaculture took the top score in health, while reservoir fisheries ranked first in literacy. A multi-dimensional approach would enhance the income and employment generation of the fishers to match with the development of the rest in the society.